Method for trapping affinity chromatography of transcription factors using aldehyde-hydrazide coupling to agarose - Jia, Yinshan (Anal Biochem, 2015)
The uses of a method of coupling DNA is investigated for trapping and purifying transcription factors. Using the GFP-C/EBP fusion protein as a model, trapping gives higher purity and comparable yield to conventional affinity chromatography. The chemistry utilized is mild and was shown to have no detrimental effect on GFP fluorescence or GFP-C/EBP DNA-binding. The method involves introducing a ribose nucleotide to the 3′ end of a DNA sequence. Reaction with mM NaIO(4) (sodium metaperiodate) produces a dialdehyde of ribose which couples to hydrazide-agarose. The DNA is combined at nM concentration with a nuclear extract or other protein mixture and DNA-protein complexes form. The complex is then coupled to hydrazide-agarose for trapping the DNA-protein complex and the protein eluted by increasing NaCl concentration. Using a different oligonucleotide with the proximal E-box sequence from the human telomerase promoter, USF-2 transcription factor was purified by trapping, again with higher purity than results from conventional affinity chromatography and similar yield. Other transcription factors binding E-boxes including E2A, c-myc, and myo-D were also purified but myogenenin and NFκB were not. Therfore, this approach proved valuable for both affinity chromatography and for the trapping approach.